2015
DOI: 10.1007/s11262-015-1174-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Middle East respiratory syndrome coronavirus (MERS-CoV) in dromedary camels in Abu Dhabi Emirate, United Arab Emirates

Abstract: High seroprevalence of Middle East respiratory syndrome corona virus (MERS-CoV) in dromedary camels has been previously reported in United Arab Emirates (UAE). However, the molecular detection of the virus has never been reported before in UAE. Of the 7,803 nasal swabs tested in the epidemiological survey, MERS-CoV nucleic acid was detected by real-time PCR in a total of 126 (1.6 %) camels. Positive camels were detected at the borders with Saudi Arabia and Oman and in camels' slaughter houses. MERS-CoV partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 11 publications
6
73
1
Order By: Relevance
“…The mixing of dromedaries underpins interaction between infectious and susceptible individuals and therefore the dynamics of MERS-CoV transmission. Live markets and abattoirs which both had higher prevalence of RNA shedding compared to other site-types in multiple studies, are key locations for animal mixing Yusof et al, 2015;Sabir et al, 2016;Miguel et al, 2017). Quantitative data describing the movement and trading patterns of dromedary populations will be essential for informing models and considering where potential vaccination should take place.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mixing of dromedaries underpins interaction between infectious and susceptible individuals and therefore the dynamics of MERS-CoV transmission. Live markets and abattoirs which both had higher prevalence of RNA shedding compared to other site-types in multiple studies, are key locations for animal mixing Yusof et al, 2015;Sabir et al, 2016;Miguel et al, 2017). Quantitative data describing the movement and trading patterns of dromedary populations will be essential for informing models and considering where potential vaccination should take place.…”
Section: Discussionmentioning
confidence: 99%
“…The available studies exhibit differences in study design, criteria for seropositivity, sample-site type and sample population characteristics. Some studies report that the latter two variables are associated with statistically significant differences in seroprevalence or prevalence of infection within individual studies Yusof et al, 2015;Sabir et al, 2016;Ali et al, 2017a, b;Miguel et al, 2017;van Doremalen et al, 2017 Implementing MERS-CoV vaccination in dromedaries will be challenging. First, since MERS-CoV infection does not cause significant disease in camels, a dromedary vaccine will be implemented solely for the purpose of preventing human infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study in Saudi Arabia by Briese et al [18] showed that the whole genome sequence of viruses obtained from humans and camels were almost identical. It was suggested that the virus is transmitted to humans via direct contact with animals, especially dromedary camels in the Middle East [14,[19][20][21][22]. Human-to-human transmission is usually via direct contact with affected individuals and is higher among household and in healthcare settings [23][24][25].…”
Section: Introductionmentioning
confidence: 99%